Oscillations in continuous culture populations of Streptococcus pneumoniae: population dynamics and the evolution of clonal suicide - Cornejo, O; Rozen, D; May, R; Levin, B (Royal Society Publishing, 2009)
Agents that kill or induce suicide in the organisms that produce them or other individuals of the same genotype are intriguing puzzles for ecologists and evolutionary biologists. When those organisms are pathogenic bacteria, these suicidal toxins have the added appeal as candidates for the development of narrow spectrum antibiotics to kill the pathogens that produce them. We show that when clinical as well as laboratory strains of Streptococcus pneumoniae are maintained in continuous culture (chemostats), their densities oscillate by as much as five orders of magnitude with an apparently constant period. This dynamic, which is unanticipated for single clones of bacteria in chemostats, can be attributed to population-wide die-offs and recoveries. Using a combination of mathematical models and experiments with S. pneumoniae, we present evidence that these die-offs can be attributed to the autocatalytic production of a toxin that lyses or induces autolysis in members of the clone that produces it. This toxin, which our evidence indicates is a protein, appears to be novel; S. pneumoniae genetic constructs knocked out for lytA and other genes coding for known candidates for this agent oscillate in chemostat culture. Since this toxin lyses different strains of S. pneumoniae as well as other closely related species of Streptococcus, we propose that its ecological role is as an allelopathic agent. Using a mathematical model, we explore the conditions under which toxins that kill members of the same clone that produces them can prevent established populations from invasion by different strains of the same or other species. We postulate that the production of the toxin observed here as well as other bacteria-produced toxins that kill members of the same genotype, 'clonal suicide', evolved and are maintained to prevent colonization of established populations by different strains of the same and closely related species.